2020
DOI: 10.1021/acs.jproteome.0c00230
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Way Interaction between Methotrexate and the Gut Microbiota of Male Sprague–Dawley Rats

Abstract: Methotrexate (MTX) is a chemotherapeutic agent that can cause a range of toxic side effects including gastrointestinal damage, hepatotoxicity, myelosuppression, and nephrotoxicity and has potentially complex interactions with the gut microbiome. Following untargeted UPLC-qtof-MS analysis of urine and fecal samples from male Sprague–Dawley rats administered at either 0, 10, 40, or 100 mg/kg of MTX, dose-dependent changes in the endogenous metabolite profiles were detected. Semiquantitative targeted UPLC-MS dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 59 publications
(118 reference statements)
1
41
0
Order By: Relevance
“…MTX can directly bind DHFR from multiple bacteria (Bolin et al, 1982), and DHFR overexpression rescues the growth of a sensitive E. coli strain (Kopytek et al, 2000). More recently, a high-throughput screen of human gut bacterial isolates identified multiple MTX sensitive strains (Maier et al, 2018), experiments in rats and mice revealed shifts in the gut microbiota in response to intraperitoneal MTX (Letertre et al, 2020;Zhou et al, 2018), and clinical studies suggest that some of the differences between the microbiomes of RA patients relative to healthy controls (Scher et al, 2013) are reversed during treatment (Zhang et al, 2015). However, it remains unclear whether the observed changes to the gut microbiota are a direct result of MTX or reflective of concomitant treatment with other medications and dietary supplements, improvement of the disease process, reduction of inflammation, and/or other confounding factors that may be present in observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…MTX can directly bind DHFR from multiple bacteria (Bolin et al, 1982), and DHFR overexpression rescues the growth of a sensitive E. coli strain (Kopytek et al, 2000). More recently, a high-throughput screen of human gut bacterial isolates identified multiple MTX sensitive strains (Maier et al, 2018), experiments in rats and mice revealed shifts in the gut microbiota in response to intraperitoneal MTX (Letertre et al, 2020;Zhou et al, 2018), and clinical studies suggest that some of the differences between the microbiomes of RA patients relative to healthy controls (Scher et al, 2013) are reversed during treatment (Zhang et al, 2015). However, it remains unclear whether the observed changes to the gut microbiota are a direct result of MTX or reflective of concomitant treatment with other medications and dietary supplements, improvement of the disease process, reduction of inflammation, and/or other confounding factors that may be present in observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the gut, both MTX-PG1 and 7-OH-MTX are transported into the cells where they are metabolized by folylpolyglutamate synthetase (FPGS) into MTX polyglutamates (MTX-PGs), which are not able to get out of cells because of their low affinity for folate transporters. MTX-PGs are subsequently reconverted by human γ-glutamyl hydrolase or bacterial glutamate carboxypeptidase II to MTX-PG1, which is again able to leave the cells [ 113 , 114 , 115 ].…”
Section: Association Between the Gm And Drugs Used For The Treatmementioning
confidence: 99%
“…These two products are inactive, so they contribute to the detoxification of the organism from MTX, which is fundamental especially in patients with delayed drug clearance and/or MTX-related adverse effects. Despite Pseudomonas (Proteobacteria), other bacteria able to synthesize glutamate carboxypeptidase II might be Prevotellaceae (Bacteroidetes) and Anaeroplasmataceae (Tenericutes); indeed, studies showed that the presence of DAMPA in the feces is positively associated with these bacterial families [ 114 ].…”
Section: Association Between the Gm And Drugs Used For The Treatmementioning
confidence: 99%
See 1 more Smart Citation
“…The relative abundance of the Firmicutes was positively correlated with the 48-h fecal excretion of 2,4-diamino-N-10-methylpteroic acid (DAMPA), a metabolite of MTX. Long-term exposure to MTX can alter the composition and function of the microbiome, which in turn affects its ability to detoxify MTX ( 69 ). MTX largely alters the human gut microbiota.…”
Section: Gut Microbiota Affects a Wide Range Of Drugs Used To Treat Almentioning
confidence: 99%